Structural Conditionality in IMF-Supported Programs. (Independent Evaluation Office Reports; Independent Evaluation Office Reports, 2008)
This evaluation examines factors influencing the effectiveness of the IMF structural conditionality in bringing about structural reform. It assesses the impact of the streamlining initiative launched in 2000 and of the 2002 Conditionality Guidelines. These guidelines aimed at reducing the volume and scope of structural conditionality by requiring 'parsimony' in the use of conditions and stipulated that conditions must be 'critical' to the achievement of the program goals. The evaluation finds that during the period 1995-2004, there was extensive use of structural conditionality in IMF-supported programs, with an average of 17 conditions per program/year.